PENGARUH LATIHAN SHOOTING DENGAN METODE BEEF TERHADAP AKURASI FREE THROW SISWI EKSTRAKURIKULER BASKET SMK NEGER 4 BANDAR LAMPUNG - Ichlasul Rizki Alamsyah; Reza Adhi Nugroho (Universitas Teknokrat Indonesia, 2022)
The purpose of this study was to determine whether there was an effect of shooting practice with the beef method on the accuracy of free throws for basketball extracurricular students at SMK Negeri 4 Bnadar Lampung. This study consisted of 15 samples with a total sampling technique using the experimental method of one groups pretest posttest. The results of the study indicate that there is a significant effect of shooting practice with the beef method with the results of the t-test count 9.909 t table 1.761. Then there is a difference after being given treatment of 2.13 from 1.87 to 4.00